Certificações aplicadas a produtos da sociobiodiversidade na Amazônia: desafios para a sustentabilidade - SOUSA, Pollyanna Coêlho de (Universidade Federal do Pará, 2024)
Certifications focused on sustainability are a series of practices that can help improve the quality of life of traditional populations in the Amazon, by providing advantages such as the use of sustainable agricultural production methods, increased productivity, reduced socioenvironmental impact, management forestry that helps conserve biodiversity and generate income. The general objective of the research was to analyze how sustainability certifications are being implemented with community organizations in the Amazon, using the cumaru almond and açaí fruit production chains as a case study. The hypothesis that motivated the research was the following: the implementation of sustainability certifications brings benefits to community organizations, which can result in a better quality of life for traditional populations in the Amazon, compared to those that do not adopt any standards. The results indicate that the benefits can be perceived in dimensions such as: Quality Management; Handler Management; Environmental management; Risk management. The use of certifications with community organizations is recommended, as long as other development models are equally recognized and respected, encouraging the promotion of inclusive and sustainable Amazon sociobiodiversity chains. It is noteworthy that it is possible that the benefits identified in community organizations that adopt some sustainability standard are related to other factors, linked to the historical and regional context, which may have resulted in more evident advances in some communities than in others.